Pengaruh Model Pembelajaran Inkuiri Terinternalisasi Ayat-Ayat Al-Qur’an terhadap Karakter Islami dan Pemahaman Konsep Kimia Peserta Didik - Maje, Fitriani; Sugiarti, Sugiarti; Wijaya, Muhammad (Program Pasca Sarjana UNM, 2019)
This study included quasi-experimental research with the research design to be used, namely Pretest-Post Control-Group Design, which aims to determine the effect of inquiry learning models internalized Qur'anic verse verses on Islamic character and understanding the participants' chemical concepts students of class XI MIA MAN 2 Barru. The research subjects were the XI MIA 2 class as an experimental class which was taught by the model of internalized inquiry of the verses of the Qur'an and the XI MIA 1 class as a control class that was taught by the inquiry model without internalizing the verses of the Qur'an. Data were analyzed descriptively and inferentially. The results showed that; 1) The average value of the Islamic character of the experimental class aspects of gratitude, honesty, courtesy, and humility in the experimental class does not have very few criteria while in the control class has less and less criteria, 2) Percentage of understanding the concept of reaction rate in the class being taught with the inquiry model internalized the verses of the Qur'an is 78 in the good category while for the class taught by the inquiry model without internalizing the verses of the Qur'an the reaction rate is 69 in the sufficient category, 3) The test results The hypothesis for Islamic characters α = 0.05 obtained a value of tcount 6.067 > ttable 2.003 and significance (0.000 < 0.05) indicating that H0 was rejected and H1 was accepted, while testing the hypothesis for understanding the concept with t-test at a significant level, α = 0.05 obtained the value of tcount 2.117 > ttable 2.003 and significance (0.034 < 0.05), indicating H0 is rejected and H1 is accepted. From the results of this study it can be concluded that the use of inquiry learning models internalized by the verses of Al'qur'an influences Islamic character and understanding of students' concepts.